Can family physicians have a role in eradication of hepatitis c infection? - Şahin, Ahmet Rıza; Erdoğan, Ayşegül; Gisi, Kadir; İspiroğlu, Murat and Ateş, Selma and Okyay, Ramazan Azim and Nazik, Selçuk and Kantarçeken, Bülent (Turkish Journal of Gastroenterology, 2020)
Background/Aims: Hepatitis C Virus (HCV) infection is an important global public health problem. The application of screening programs is important for the elimination of HCV in addition to DAA therapies. The aim of this study was to measure the knowledge, attitudes and behaviours of family physicians, who are important in screening programs for the diagnosis, natural history, and treatment of HCV infection. Materials and Methods: This cross-sectional study aimed to measure the knowledge levels in respect of HCV screening, diagnosis, natural history and treatment, of family physicians working nationwide in Turkey, through a survey. Results: The most common reason to perform an anti-HCV test stated by 70.9% (n:420) of the participants was the mandatory screening program before marriage. Of the participants included in the study, 29.6% (n=175) had encountered anti-HCV test positivity at least once within the last year, and of these, 15.4% (n=27) had no knowledge of whether the patient went to a higher level center for further diagnosis, while 58.9% (n=103) did not know the disease stage. In response to questions about current drug options for hepatitis C infection, 14.5% were aware of DAA and 34.8% of participitant reported interferon+ ribavirin. Conclusion: Family physicians have gaps in their knowledge of the screening, natural history and treatment of HCV infection. The results of this study show that HCV training plans for family physicians should cover all aspects of the infection, and emphasize the necessity for the establishment of guideline-based screening recommendations.